Metabolism and Neurotoxicity of Homocysteine Thiolactone in Mice: Evidence for a Protective Role of Paraoxonase 1 - Borowczyk, Kamila (2012)
Homocysteine (Hcy)-thiolactone is toxic, induces epileptic seizures in rodents, and has been implicated in Alzheimer’s disease. Paraoxonase 1 (Pon1), a component of high-density lipoprotein, hydrolyzes Hcy-thiolactone in vitro. Whether this reflects a physiological function and whether Pon1 can protect against Hcy-thiolactone toxicity was unknown. Here we show that Hcy-thiolactone was elevated in brains of Pon1(−/−) mice (1.5-fold, p = 0.047) and that Pon1(−/−) mice excrete more Hcy-thiolactone than wild type animals (2.4-fold, p = 0.047). The frequency of seizures induced by intraperitoneal injections of L-Hcy-thiolactone was significantly higher in Pon1(−/−) mice compared with wild type animals (52.8% versus 29.5%, p = 0.042); the latency of seizures was lower in Pon1(−/−) mice than in wild type animals (31.8 min versus 41.2 min, p = 0.019). Using the Pon1 null mice, we provide the first direct evidence that a specific Hcy metabolite, Hcy-thiolactone, rather than Hcy itself is neurotoxic in vivo. Our findings indicate that Pon1 protects mice against Hcy-thiolactone neurotoxicity by hydrolyzing it in the brain, and suggest a mechanism by which Pon1 can protect against neurodegeneration associated with hyperhomocysteinemia and Alzheimer’s disease.